How much is CEO education worth to a firm? Evidence from European firms - Morresi, Ottorino (PSL Quarterly Review, 2017)
The emergence of an industry dedicated to evaluating the quality of university institutions around the world makes it possible to analyze whether students who graduate from highly-ranked schools perform better during their working lives. We focus on the education of CEOs who lead European listed firms, and analyze its impact on firm performance. If better schools produced better managers, we should find better firm performance for the firms led by managers who have graduated from highly-ranked schools. However, we do not find clear support for this claims, and rather our analysis shows that the ranking position of a university is not significantly linked to firm performance. Moreover, we find that the results of any such estimate are highly sensitive to the performance measure used and the type of ranking chosen. "QS University Rankings" and "Times Higher Education University Rankings" produce results that are more in line with our assumption. Unlike accounting ratios, market-based performance measures tend to provide stronger support for our hypothesis. JEL codes: G34; I26; J24